Effect of vesicular arbuscular mycorrhizal association on 'S 1' mulberry (Morussp) at nursery stage - SETUA, G C; SUDHAKAR, P; KAR, R; DAS, N K; GHOSH, J K (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1995-97 to study the effect of YAM inoculation on survivability, growthcharacters, leaf yield and phosphorus uptake in'S I' mulberry saplings at nursery stage. Data of 4'1/2 - month - oldmycon'hized saplings revealed'that except leaf moisture, leaf and root dry-matter, others were found to be significantat 1 % level and indicated increase in survival by 10.4%, plant height by 5.7%, leaf area by 11.8%, root length by 9.8%,number of lateral roots/plant by 56.1% and plant dry biomass by 27.4% over control. Phosphorus uptake was alsoenhanced by 13,5% and tukra infestation was found considerably less (8% only at +1 scale) compared to non-mycorrhizedsaplings, Since fhe overall perfOrmance of mycorrhized saplings was better in respect of some important qualitativeand quantitative characters of mulberry, the method may be exploited to raise VAM-colonized mulberry saplings fornew plantation.